The Influence of The Rupiah Exchange Rate and Gold Exchange on The Banking Sector Stock Price Index on The Indonesian Stock Exchange In 2020-2023 - Elma Abnaina; A. Firsa Ariza; Zahrah Rahmawati; Avriluna Dewi (Magister Administrasi Bisnis ULM, 2024)
Abstract: Share prices are used to see the value of the company. If the share price of a company is classified as high, then it can be said that the company's value is in good condition. This research aims to determine the influence of the rupiah and gold exchange rates on share prices in the banking sub-sector listed on the Indonesian Stock Exchange (BEI) in 2020-2022. This research uses quantitative methods, the population of this research is 30 companies and the sample taken is 10 companies according to the criteria. Data is taken using Purpose Sampling techniques, types of data using secondary data, data analysis using multiple linear analysis. The research results show that the rupiah exchange rate has a positive effect on the share prices of banking companies listed on the Indonesian stock exchange, gold has a positive effect on the share prices of banking companies listed on the Indonesian stock exchange